The Influece of Qur’an Learning Methods and Learning Concentration Toward in Early Reading and Wraiting the Qur’an Abilities - Setiawan, Eko (ACIECE, 2017)
The purpose of this study is to know the influence of Qur’an learning methods and learningconcentration toward in early reading and writing the Qur'an abilities. This study is conducted inkindergarten Aisyiyah 12 and 19 West Java, 2016. This study is using the experimental methodto the design of treatment by the level of 2x2. The results of the study, the early abilities ofQur’an reading and writing children different between using the methods of Al-Bana and usingAl-Bayan. The result can be seen in the average of score, of the Al-Bana method 34.18, and theusing of Al-Bayan method 31.25. There is significant difference between the Qur’an learningmethod and learning concentration toward in early reading and writing the Qur'anabilities.Conclusion (1) There are significant differences between the effects of Qur’an learning methodof Al-Bana and Al-Bayan method toward in early reading and writing the Qur’an abilities, (2)There is an interaction between the Qur’an learning method and learning concentration on theearly of Qur’an reading and writing abilities, (3) for a group that have a high learningconcentration and using the Al-Bana method is higher than the group that have a high learningconcentration that using the Al-Bayan method on the early of Qur'an reading and writingabilities, (4) for the group using of Al-Bana method and have a low learning concentration inearly reading and writing the Qur'anabilities is lower than the group that using of the Al-Bayanmethod and have a low learning concentration.